2013
DOI: 10.1371/journal.pntd.0002270
|View full text |Cite
|
Sign up to set email alerts
|

Ecology of Leptospira interrogans in Norway Rats (Rattus norvegicus) in an Inner-City Neighborhood of Vancouver, Canada

Abstract: Background Leptospira interrogans is a bacterial zoonosis with a worldwide distribution for which rats (Rattus spp.) are the primary reservoir in urban settings. In order to assess, monitor, and mitigate the risk to humans, it is important to understand the ecology of this pathogen in rats. The objective of this study was to characterize the ecology of L. interrogans in Norway rats (Rattus norvegicus) in an impoverished inner-city neighborhood of Vancouver, Canada.Methodology/Principal FindingsTrapping was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
101
3
9

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(131 citation statements)
references
References 28 publications
15
101
3
9
Order By: Relevance
“…Additionally, the built environment within the study area is relatively homogeneous (high-density, mixed-use urban) and does not clearly account for observed heterogeneity in pathogen distribution. It is interesting to note that similar clustering was also observed for Leptospira interrogans carriage in these rat populations and likewise could not easily be explained by environmental factors or rat phenotypic characteristics (Himsworth et al 2013b).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Additionally, the built environment within the study area is relatively homogeneous (high-density, mixed-use urban) and does not clearly account for observed heterogeneity in pathogen distribution. It is interesting to note that similar clustering was also observed for Leptospira interrogans carriage in these rat populations and likewise could not easily be explained by environmental factors or rat phenotypic characteristics (Himsworth et al 2013b).…”
Section: Discussionsupporting
confidence: 64%
“…For tissue-based PCR screening, 630 samples were considered to be the optimal sample size to calculate pathogen prevalence accurately in each city block (Himsworth et al 2013b), although additional samples were included where resources allowed. The specific samples to be tested were selected randomly.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, we found L. interrogans in Palena, Alto Rio Cisnes, and Isla Magdalena, which is a Leptospira species largely associated to rodents (Himsworth et al 2013). In addition, we found L. borgpetersenii in Liquiñe, Neltume, Lake Todos los Santos, and Alto Rio Cisnes, which is a Leptospira species associated with cattle farming.…”
Section: Resultssupporting
confidence: 50%
“…The ecology of rats and the epidemiology of L. interrogans within their populations are intimately connected ( 4 ). Previous research on other reservoir species suggests that anthropogenic disturbances may alter reservoir ecology, resulting in new transmission patterns ( 5 , 6 ).…”
mentioning
confidence: 99%